(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
In March 2016, the Balkan Route was closed; the refugees and migrants continued transiting through the Republic of North Macedonia, using irregular means to reach the desired destination. Although the institutions were monitoring and controlling the south border with the help of the Army and foreign police officers from the EU Member States on grounds of bilateral agreements, a great number of the refugees and migrants used the services of smugglers, exposing themselves to risk upon their health, safety and freedom. This required amendment and adoption of new regulations which relate to the asylum system. The aim of this article is to make a comprehensive overview of the various practices, policies, and procedures in relation to the borders’ control and migration policies in the Republic of North Macedonia. The article emphasizes the key challenges faced by the asylum seekers and the refugees during the asylum procedure and during realization of other rights. An analysis is made of the current legal framework and corpus of laws regulating entry and exit in the territory, security of borders and borders’ management as well as laws regulating the rights and status of foreigners in the country. A particular emphasis is given to asylum procedures and policies to accommodate.